Association of De Novo RNF213 Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. (30th March 2021) - Pinard, Amélie; Fiander, Maximillian D.J.; Cecchi, Alana C.; Rideout, Andrea L.; Azouz, Mohamed; Fraser, Stuart M.; McNeely, P. Daniel; Walling, Simon; Novara, Sarah C.; Hurst, Anna C.E.; Guo, Dongchuan; Parkash, Sandhya; et al.
Abstract : Objective: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. Methods: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. Results: We identified 3 novel rare de novo RNF213 variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4, 114–4, 120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. Conclusions: These results indicate a novel syndrome associated with RNF213 rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4, 114 to 4, 120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.